Historical Processes of Power, Knowledge, and Identity Change in Gurungs: With Relevancy to Identity Conflict and Modern Debates in Nepal - Gurung, Mani Raj (Patan Prospective Journal, 2023)
The major theme of this paper is to demystify prior theoretical concepts of cultural identity in Gurungs and tries to establish new arguments regarding identity. Most of the previous theoretical contributions found that identity always remains the same and is fixed in a single blood, land, or territory. However, this paper claims that identity cannot be understood as a fixed form, it is always changed and constructed in a historical time frame. Even different forms of cultural and ritual practices in societies have been created in certain time frames and are also being changed. Based on this, the construction of Gurungs’ identity was the consequence of long historical processes and power formation. Recently, many social scientists have argued that culture and identity should not be understood as observing the only objective reality but need to be subjected. It can be interpreted as understanding the long historical migratory processes, contacting different clans, and groups, studying the historical power formations, new knowledge establishments, economic relations, and changes. Gurungs’ identity and culture can only be interpreted by understanding the historical migratory roots in the northern foothills from Mt. Kailash to Kaski, Lamjung, and Gorkha and contact with different kings’ (local king (Kroh) powers, Ghale king powers, Hindu kings’ powers, and modern economic powers) and their formation of knowledge in a historical timeframe. Power is the major key factor in the creation of culture and identity but it does not mean only political power, rather understood as established new knowledge formation in the society.